Depleted Monolithic Pixels (DMAPS) in a 150 nm technology: lab and beam results. (23rd January 2017) - Obermann, T.; Hemperek, T.; Hügging, F.; Krüger, H.; Pohl, D.-L.; Schwenker, B.; Wermes, N.
Abstract: The fully depleted monolithic active pixel sensor (DMAPS) is a new concept integrating full CMOS circuitry onto a fully depletable silicon substrate wafer. The realization of prototypes of the DMAPS concept relies on the availability of multiple well CMOS processes and high resistive substrates. The CMOS foundry ESPROS Photonics offers both and was chosen for prototyping. Two prototypes, EPCB01 and EPCB02, were developed in a 150 nm process on a high resistive n-type wafer of 50 μm thickness. The prototypes have 352 square pixels of 40 μm pitch and small n-well charge collection node with very low capacitance ( n + -implantation size: 5 μm by 5 μm) and about 150 transistors per pixel (CSA and discriminator plus a small digital part).